Fracture characterization of recycled high density polyethylene/nanoclay composites using the essential work of fracture concept. Issue 2 (12th December 2015) - Na, Sukjoon; Spatari, Sabrina; Hsuan, Yick G.
Abstract : The effect of nanoclay on the plane‐strain fracture behavior of pristine High density polyethylene (HDPE) and recycled HDPE blends was studied using the essential work of fracture (EWF) concept. The failure mode of EWF tested specimens was found to be associated with the specific non‐EWF ( βB wp, B ). Adding 6‐wt% of nanoclay to pristine HDPE and 2‐wt% to recycle‐blends greatly decreased the βB wp, B values and led to a transition from ductile to brittle failure mode. A fractographic study revealed that the difference in failure modes was caused by the changes in micro and macro morphologies, which could be related with the specific EWF ( we, B ). In the ductile failure, we, B is governed by the fibril size; adding nanoclay and recycled HDPE to pristine HDPE decreased the fibril size and subsequently lowered the we, B value. In the brittle failure, the we, B value was enhanced by creating a rough fracture surface. Adding nanoclay to pristine HDPE, a steadily decrease in we, B was measured until 4‐wt% after which the change was insignificant. Conversely, nanoclay content more than 2‐wt% in recycle‐blends greatly decreased the we, B value. A transition map was constructed to illustrate the potential failure mode and the associated fracture morphology based on the tested material compositions. POLYM. ENG. SCI., 56:222–232, 2016. © 2015 Society of Plastics Engineers